Geodiversity map of the Tatra National Park for geotourism - Zwoliński, Zbigniew; Stachowiak, Jakub (Quaestiones Geographicae, 2012)
The paper indicates the relations between geodiversity and geotourism in the Tatra National Park. Geodiversity of the Tatra Mountains is visualized by its geodiversity map, whereas geotouristic attractions are measured by touristic attractions along touristic trails on geodiversity map. Areas of the highest geodiversity cover merely 8.2% of the Tatar National Park area. These are mainly areas close to the Tatra Mountains' main ridge. It is so due to geology, landform energy, slopes, landform fragmentation and geoecological belts. Most of the analyzed thematic layers categorizes ridges as more geodiversed than valley areas. The trails situated in the valley bottoms usually cross by areas of low geodiversity, however, from geotouristic point of view, it should be noted that slopes and ridges circumvolving the valley can be marked by high geodiversity. The mountain slopes and ridges are within tourist's sight, what increases trail's geotouristic attractiveness. Amongst many geotouristically interesting parts of the Tatra Mountains Dolina Pięciu Stawów valley appears to be the most appealing with its high quantity and high variety of post-glacial forms on valley's bottom as well as on its slopes.